Complications Associated With Nasogastric Tube Placement in the Acute Phase of Stroke: A Systematic Review. Issue 4 (August 2018) - Nascimento, Ana; Carvalho, Mariana; Nogueira, Jerina; Abreu, Pedro; Nzwalo, Hipólito
Abstract : ABSTRACT: This systematic review explores the frequency of complications associated with nasogastric tube (NGT) placement in patients with acute stroke. The unique condition of the dysphasic, immobile, confused immunosuppressed patient who has had an acute stroke hampers any consistent inference from other neurological or nonneurological condition in which NGT placement is used. Twelve studies including 921 patients fed by NGT in the acute phase (first 4 weeks) were included in the analysis. The overall quality of the included studies was good. The main limitation was the heterogeneity and small size of most studies. The occurrence of NGT placement failure and malposition, hypoxemia, and regurgitation was addressed in the selected studies. Recurrent NGT dislodgement and a combination of tube dislodgement and blockage of the tube were the main reasons for NGT placement failure. In the absence of chronic hypoxemic pulmonary or cardiac disorders, NGT feeding was not associated with clinically significant hypoxemia in patients who have had an acute stroke. Data are scarce on the topic. Research about the frequency of local and systemic NGT complications and strategies for prevention will certainly contribute to enhance evidence-based management of dysphagia in acute stroke. Abstract : Supplemental digital content is available in the text.